Second-tier elections and electoral districts in democratic Portugal, 1975-2004 - Freire, André (2005)
This research explores the relationships between the electoral behaviour of the Portuguese in parliamentary, local and European elections in the period from 1975 to 2004. It looks at the development of the party system and at aggregate volatility levels in different types of election. For individual voters it compares the social and political factors affecting voter choice of party in different types of election. We tested theories on election cycles by comparing the overall electoral results of different types of election at different periods of the election cycle, taking as our point of departure the winners of each of the preceding parliamentary elections. The main conclusion is that the relationships between second-tier and first-tier elections reflect not only short-term effects, but also long-term ones.